REPUTASI CEO TERHADAP KEBERLANGSUNGAN USAHA PERUSAHAAN - Agustin, Ika Dyah Ayu; Bhilawa, Loggar (Jurnal Akuntansi AKUNESA, 2020)
This study aims to examine the effect CEO?s Reputation using component namely Age, Education, and Experience on the measured Firm?s Going Concern using four components, namely Profitability, Liquidity, Market Share, and Operational Cash Flow. This studies uses Multiple Linear Regression. The research sample is 339 companies from registered at Bursa Efek Indonesia (BEI). The result of the study show that CEO?s Reputation using 3 components, namely age, education, and experience has an effect on the Firm?s Going Concern. This due to Age, education, and exprerience influence strategic and policy decisions taken by A CEO. The decissions regarding the strategic and policy taken by A CEO has an impact on firm?s financial performance which in turn will affect the firm?s ability to maintain business continuity.